Prospects of development of the cruise ship tourism market – the case study of the Baltic Sea region - Kizielewicz, Joanna (Perspektywy rozwoju morskiej żeglugi wycieczkowej – przykład regionu Morza Bałtyckiego, 2019)
In 2018 the cruise ship tourism market generated 35.5 bn USD and in the Baltic Sea Region (BSR) the rate of growth is more significant compared to other markets in the world. The figures, provided by Cruise Baltic, prove that in 2018 cruise ships carried 5.8 million passengers, which constitutes 7.7% of the average annual growth in the number of passengers carried within the BSR. The share of cruise ship tourism market in the BSR in the global market, amounts to 11.7 %. The aim of this article is to assess the potential of the BSR regarding the development of cruise ship tourism and to indicate trends for the development of this market. The study included both exploratory method and “desk research” method. In the analysis of the study results the author used quantitative and qualitative methods. The results of the research may constitute interesting study material for the entities directly and indirectly related to the cruise ship tourism market
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 244-255
Keywords: cruise tourism; Baltic Sea Region; żegluga wycieczkowa; Region Morza Bałtyckiego